Effect of Earthworm Coelomic Fluid on Inhibition Activity Against Some Pathogenic Bacteria - Zaid Naji Hassan (Journal of Global Pharma Technology, 2019)
In the present study , coelomic fluid tested for antibacterial activates. four different concentration of coelomic fluid was used (100%,75%, 50%,25%)which was determine by  the agar well diffusion method and tested against five pathogenic bacteria isolates (E. coli , K. pnemoniae, Staph. eureus, Staph. epidermis, Ps. aeruginosa). coelomic fluid show highest inhibition zone aganist E.coli at concentration (100%,75%,50%) ,while staph eureus show highest inhibition at concentration (25%).Keywords: Coelomic fluid, Earthworm, Bacteria.